Assays with Detection of Fluorescence Anisotropy: Challenges and Possibilities for Characterizing Ligand Binding to GPCRs. (February 2018) - Rinken, Ago; Lavogina, Darja; Kopanchuk, Sergei
Abstract : Binding of fluorescent ligands (tracers) to their target receptors can be directly monitored over time, as the binding of a low-molecular-weight (LMW) tracer to a larger particle causes an increase of fluorescence anisotropy (FA). The combination of bright fluorophores, tracers with low nonspecific binding, and budded baculovirus particles (BVPs) for overexpression of G protein-coupled receptors (GPCRs) ensures a high signal-to-noise ratio in FA assays. The obtained data enable quantitative assessment of equilibrium binding and kinetic parameters for both the tracer and competing compounds as well as an estimation of the receptor concentration. FA assays have clear potential for implementation in drug screening systems, but also in studies of ligand-binding mechanisms for particular GPCRs. Trends: Assays with detection of fluorescence anisotropy (FA) enable monitoring of the association and dissociation of fluorescent ligands to/from G protein-coupled receptors (GPCRs) with conventional spectrofluorimeters without the need to separate bound tracer from free tracer. Baculoviruses can be used for transfection of insect cells with a GPCR of interest, which is then taken up by the budding virus particles. The latter can be used as a receptor preparation for ligand-binding studies. The low sedimentation rate and even size make them especially suitable for homogeneous assays. The high-quality data obtained with FA assays enable not only assessment of the affinities of the tracer and competing ligands but also the establishment of kinetic parameters for both fluorescently labeled and non-labeled compounds, which emphasizes the potential of FA assays in high-throughput drug screening as well as in studies of ligand-binding mechanisms with particular GPCRs.